2021
DOI: 10.1002/adfm.202108574
|View full text |Cite
|
Sign up to set email alerts
|

Cu12Sb4S13 Quantum Dots/Few‐Layered Ti3C2 Nanosheets with Enhanced K+ Diffusion Dynamics for Efficient Potassium Ion Storage

Abstract: Despite the high theoretical specific capacity of transition-metal disulfides anode for potassium-ion batteries (PIBs), their development has been greatly hindered by dramatic capacity fading and poor cycle life. Herein, the synthesis of the new composite of Cu 12 Sb 4 S 13 quantum dots/few-layered Ti 3 C 2 nanosheets (CAS-Ti 3 C 2 ) as advanced anode for boosting the K ion storage is reported. It is found that as-made CAS-Ti 3 C 2 show a strong synergistic effect between quantum dots and Ti 3 C 2 nanosheets m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The long-term cycle performance of the previously reported ternary chalcogenide-based (such as CuSbS 2 , FeCoS 2 , BiSbS 3, and AgBiS 2 ) has not exceeded 1000 cycles, except Cu 12 Sb 4 S 13 (Figure 2i). [4,[40][41][42][43] To confirm the phase transition of the Cu 3 BiS 3 electrode during the charging/discharging process, ex situ XRD analysis was performed at six different potentials, as shown in Figure 3a and Table S1 (Supporting Information). First, it can be observed that some fixed peaks are attributed to Al foil, and partially oxidized CuO .…”
Section: Resultsmentioning
confidence: 99%
“…The long-term cycle performance of the previously reported ternary chalcogenide-based (such as CuSbS 2 , FeCoS 2 , BiSbS 3, and AgBiS 2 ) has not exceeded 1000 cycles, except Cu 12 Sb 4 S 13 (Figure 2i). [4,[40][41][42][43] To confirm the phase transition of the Cu 3 BiS 3 electrode during the charging/discharging process, ex situ XRD analysis was performed at six different potentials, as shown in Figure 3a and Table S1 (Supporting Information). First, it can be observed that some fixed peaks are attributed to Al foil, and partially oxidized CuO .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the synthesis of the Cu 12 Sb 4 S 13 QDs/Ti 3 C 2 (CAS-Ti 3 C 2 ) as novel anode for improving the K + storage was presented. [140] The as-obtained CAS-Ti 3 C 2 exhibited a strong synergistic effect due to the formation of TiS bond (Figure 4e,f), and then the diffusion path of K + can be shortened (Figure 4g) as well as alleviating the volumetric expansion during the charging-discharging process. Therefore, this novel composite anode shows a remarkable reversible specific capacity as well as excellent cycling performance for Potassium-ion batteries (PIBs).…”
Section: Effects Of Qds For Energy Storagementioning
confidence: 97%
“…Moreover, developing bimetal sulfide QDsbased anodes for PIBs can promote its cycle life. Cao et al [140] reported the synthesis of Cu 12 Sb 4 S 13 QDs/Ti 3 C 2 nanosheets (CAS-Ti 3 C 2 ) composite as anode for improving the potassium storage (Figure 22g-i). The composite showed a synergistic effect between QDs and Ti 3 C 2 sheets due to the presence of TiS bond, which can significantly shortened the diffusion path of K + and suppressed the volume change during the cycling reaction.…”
Section: Alkali-metal Ion Batteriesmentioning
confidence: 99%
See 2 more Smart Citations